Impaired Glucose Metabolism in Liver Cirrhosis - Suzanna Ndraha; Fendra Wician; Marshel Tendean; Ivan DP Sunardi; Mardi Santoso (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Approximately 30% of patients who suffer cirrhosis maybe diabetic, called hepatogenous diabetes (HD). Insulin resistance seems to be the pathophysiologic basis for HD. Aims of this study were to evaluate the glucose metabolism disorders in liver cirrhosis patients and to observe the insulin resistance in HD.Method: This study was conducted from February-July 2013 in Koja Hospital Jakarta. In the first phase, with observational design, inclusion criteria were liver cirrhosis and exclusion was an acute complication. We recorded their oral glucose tolerance test (OGTT). Patients who met the HD criteria were continued to the second phase, using analytic design, and were compared with type 2 diabetes mellitus (T2DM) patients as control. Mean differences of 2-hours postprandial plasma glucose/fasting plasma glucose (2hPPG/FPG) ratio, as well as fasting insulin levels between both groups were assessed.Results: Twenty four patients were included in our study. Normal glucose tolerance test were noted in 7 (29%) patients, impaired glucose tolerance (IGT) in 6 (25%) patients and HD in other 11 (46%) patients. In the second phase, we obtained the ratio of 2hPPG/FPG in HD was 2 ± 0.5 and T2DM was 1.5 ± 0.4 (p = 0.01). Mean fasting insulin levels in HD was 10.8 ± 4.2 μIU/mL, while T2DM was 9.3 ± 5.3 μIU/mL (p = 0.5). The ratio of 2hPPG/FPG was higher in HD compared to T2DM, assuming the role of insulin resistance in HD.Conclusion: There were impaired glucose metabolism in liver cirrhosis patients, as well as hepatogenous diabetes. Insulin resistance and hyperinsulinemia appeared to play role in HD.Keywords: hepatogenous diabetes, type 2 diabetes mellitus, 2hPP/FPG ratio, fasting insulin level